Analysis of risk factors associated with freezing of gait in de novo drug-naive Parkinson's disease patients. - ZHANG, Zhe-hao; LIU, Wei-guo; ZHOU, Hao; LI, Jing-zhe; HUANG, Xiao-ran (Chinese Journal of Contemporary Neurology & Neurosurgery, 2026)
Objective To investigate the prevalence, clinical characteristics and neuroimaging mechanisms of freezing of gait (FOG) in de novo drug-naive patients with Parkinson's disease (PD), and to identify the risk factors for FOG in these patients. Methods A total of 250 de novo drug-naive PD patients treated at The Affiliated Brain Hospital of Nanjing Medical University from October 2018 to September 2024 were retrospectively enrolled. According to item 14 score of Unified Parkinson's Disease Rating Scale II (UPDRS II), the PD patients were divided into the FOG group (score ≥ 1, n = 45) and the non-FOG (nFOG) group (score = 0, n = 205). In addition, 55 gender, age and education matched healthy volunteers were included as healthy controls. The global cognitive function of all subjects was assessed using the Montreal Cognitive Assessment (MoCA), the severity of depressive symptoms was evaluated with the Hamilton Depression Rating Scale (HAMD), and the severity of anxiety symptoms was measured by the Hamilton Anxiety Rating Scale (HAMA). For PD patients, the activities of daily living were assessed using UPDRS II, the severity of core motor impairment was evaluated with Unified Parkinson's Disease Rating Scale III (UPDRS III), the disease stage and progression were assessed using the modified Hoehn-Yahr stage, and non-motor symptoms and their burden were evaluated using the Non-Motor Symptoms Questionnaire (NMSQ). T1WI and resting-state fMRI data were acquired, and the gray matter volume was extracted for analysis. The spontaneous brain activity levels were analyzed using the amplitude of low-frequency fluctuation (ALFF) algorithm. Univariate and multivariate stepwise Logistic regression analyses were performed to identify the risk factors for FOG in PD patients. Results The prevalence of FOG in de novo drug-naive PD patients was 18% (45/250). No statistically significant differences in gray matter volume were found among the control group, FOG group and nFOG group (adjusted P > 0.05, for all). Statistically significant differences were detected in Z-score normalized amplitude of low-frequency fluctuation (zALFF) values of the right inferior parietal lobule (F = 14.961, P = 0.000) and right calcarine gyrus (F = 14.539, P = 0.000) among the 3 groups. Further pairwise comparisons showed that compared with the control group, the nFOG group exhibited decreased zALFF value in the right calcarine gyrus (t = 5.305, adjusted P = 0.000), the FOG group presented increased zALFF value in the right inferior parietal lobule (t =-5.029, adjusted P = 0.000) and decreased zALFF value in the right calcarine gyrus (t = 3.946, adjusted P = 0.000); while compared with the nFOG group, the FOG group had a higher zALFF value in the right inferior parietal lobule (t = -4.974, adjusted P = 0.000). Logistic regression analysis showed that a higher UPDRS II score (OR = 1.365, 95%CI: 1.227-1.518; P = 0.000) and zALFF value in the right inferior parietal lobule (OR = 5.021, 95%CI: 2.116-11.915; P = 0.000) were risk factors for FOG in PD patients. Conclusions FOG can also occur in patients with early-stage PD. A high UPDRS II score and abnormally increased zALFF value in the right inferior parietal lobule are risk factors for FOG in early-stage PD patients.